Electrochemical measurements of 1D/2D/3DNi-Co bi-phase mesoporous nanohybrids synthesized using free-template hydrothermal method. (10th June 2018) - Guellati, O.; Harat, A.; Momodu, D.; Dangbegnon, J.; Romero, T.; Begin, D.; Pham-Huu, C.; Manyala, N.; Guerioune, M.
Abstract: In this study, a facile and low cost free-template hydrothermal precipitation method was used to synthesize mesoporous Ni-Co based bimetallic carbonates (CO3 ) 2- and/or hydroxides (OH) − micro/nanostructures with different morphologies (1D, 2D and 3D) based on variant stoichiometric compositions. The effect of the growth temperature, synthesis time as well as the Ni/Co-precursors ratio on the physico-chemical properties and faradic electrochemical behavior of these products was investigated. The as-obtained bi-phase nanohybrids were characterized extensively structurally and morphologically. The textural analysis results confirmed the presence of mesoporous products with a BET-SSA ∼50 m 2  g −1 (0.52 cm 3  g −1 pore volume) for the 3D urchin-like structure and a BET-SSA ∼ 47.14 m 2  g −1 (0.31 cm 3  g −1 pore volume) was obtained for the 2D nanoflakes structure. The electrochemical measurements performed in a 6.0 MKOH aqueous electrolyte depicted excellent electrochemical performance ascribed to the optimized composition of Ni-Co LDH (or α-Ni(OH)2 ) with Co2 (OH)3 Cl and their unique hierarchical mesoporous nanoflake and urchin-like architectures. In addition, an exceptionally notable specific capacitances (capacities) of 1700 F g −1 (161 mAh.g −1 ) and 1379 F g −1 (192 mAh.g −1 ) were obtained for both structures at 5 mV s −1 scan rate (0.5 A g −1 gravimetric current density) respectively. These are much better than mono - hydroxides synthesized in same conditions with 351 F g −1 (90 mAh.g −1 ) for Ni and 216 F g −1 (21.5 mAh.g −1 ) for Co. A good cyclic stability of ∼98% after 2000 charge-discharge cycles at 30 A g −1 was recorded depicting their potential as suitable materials for energy storage devices. Graphical abstract: Highlights: Ni/Co-precursor ratio effect on the template-free hydrothermal growth of carbonate and/or hydroxide nanocomposites. Ni/Co-content ratio effect on electrochemical performance of Ni-Co based multiphase nanocomposites. D/2D/3D architecture microstructures of Ni-Co bi-phase nanohybrids as promising candidates for electrodes in supercapacitor application.